Periodic FTO IOs/CdS NRs/CdSe Clusters with Superior Light Scattering Ability for Improved Photoelectrochemical Performance. Issue 6 (9th January 2020) - Wang, Zhiwei; Nguyen, Tam Duy; Yeo, Loo Pin; Tan, Chiew Kei; Gan, Lin; Tok, Alfred Iing Yoong
Abstract: Periodic fluorine‐doped tin oxide inverse opals (FTO IOs) grafted with CdS nanorods (NRs) and CdSe clusters are reported for improved photoelectrochemical (PEC) performance. This hierarchical photoanode is fabricated by a combination of dip‐coating, hydrothermal reaction, and chemical bath deposition. The growth of 1D CdS NRs on the periodic walls of 3D FTO IOs forms a unique 3D/1D hierarchical structure, providing a sizeable specific surface area for the loading of CdSe clusters. Significantly, the periodic FTO IOs enable uniform light scattering while the abundant surrounded CdS NRs induce additional random light scattering, combining to give multiple light scattering within the complete hierarchical structure, significantly improving light‐harvesting of CdS NRs and CdSe clusters. The high electron collection ability of FTO IOs and the CdS/CdSe heterojunction formation also contribute to the enhanced charge transport and separation. Due to the incorporation of these enhancement strategies in one hierarchical structure, FTO IOs/CdS NRs/CdSe clusters present an improved PEC performance. The photocurrent density of FTO IOs/CdS NRs/CdSe clusters at 1.23 V versus reversible hydrogen electrode reaches 9.2 mA cm −2, which is 1.43 times greater than that of CdS NRs/CdSe clusters and 3.83 times of CdS NRs. Abstract : Periodic fluorine‐doped tin oxide inverse opals (FTO IOs) grafted with CdS nanorods (NRs) and CdSe clusters are developed as a hierarchical photoanode for improved photoelectrochemical (PEC) performance. Various enhancement strategies that are incorporated in this hierarchical photoanode, such as heterojunction formation, conductive skeleton, and multiple light‐scattering, are vital to the enhancement of PEC performance.